Frequency of Testing for Clostridioides difficile in Long-Term Care Facilities in Louisville, Kentucky. (October 2020) - Angulo, Frederick; Pena, Senen; Carrico, Ruth; Stephen, Furmanek; Joann, Zamparo; Gonzalez, Elisa; Gray, Sharon; Ford, Kimbal; Ferreira, Catia; Ramirez, Julio
Abstract : Background: Clostridioides difficile infection (CDI), caused by toxigenic C. difficile and predominately manifested by moderate-to-severe diarrhea, is an important cause of morbidity and mortality in long-term care facilities (LTCFs). However, for CDI to be diagnosed in an LTCF resident, an LTCF resident with diarrhea must have a stool specimen collected for CDI diagnostic testing. The objective of this study was to define the frequency of stool specimen collection and testing for CDI in adult LTCF residents with diarrhea in Louisville, Kentucky. Methods: A cross-sectional study was conducted in 14 (31%) of the 45 LTCFs in Louisville (adults aged ≥18 years; population, 599, 276) to identify LTCF residents with diarrhea and to observe the frequency of stool specimen collection for CDI diagnosis. For 14 consecutive days in February 2019, each LTCF was visited to identify new onset diarrhea (≥3 loose stools in 24 hours) by interviews of nursing staff. For residents with diarrhea, staff reviewed electronic medical records to determine whether a stool specimen was collected for CDI diagnosis and interviewed nurses about potential noninfectious causes of diarrhea. Results: The 14 participating LTCFs have 1, 208 beds (median, 86 beds and 43 occupied beds per participating LTCF). Among 743 LTCF residents (with 10, 402 patient days of surveillance), new-onset diarrhea was identified in 63 residents (21% male; median age 75 years); 0.6 diarrhea cases per 100 patient days (diarrhea attack rate, 0.6% per day). Nurses indicated that 16 (25%) of the 63 residents with diarrhea had a potential noninfectious cause of diarrhea (11 laxatives, 3 feeding tube, 1 colostomy, and 1 gastric surgery). Stool specimens were collected for CDI testing from 20 of 63 of residents (32%) with diarrhea; none with potential noninfectious cause of diarrhea and from 20 of 47 other residents (42%) with diarrhea. Of 20 stool specimens tested, 9 (47%) yielded toxigenic C. difficile (8.6 CDI cases per 10, 000 patient days). During this survey, none of the 63 LTCF residents with diarrhea were transferred to a hospital or other healthcare facility. Conclusions: Diarrhea was common among LTCF residents, and toxigenic C. difficile was frequently identified in stool specimens collected from LTCF residents with diarrhea. The majority of non–laxative-receiving LTCF residents with diarrhea did not have a stool specimen collected for CDI diagnosis. The low frequency of CDI diagnostic testing of LTCF residents with diarrhea indicates that CDI may be underdiagnosed in these LTCFs and suggests that the CDI disease burden may be larger than currently appreciated. Funding: Pfizer Vaccines provided support for this study. Disclosures: Frederick Angulo, Kimbal D. Ford, Joann Zamparo, Elisa Gonzalez, Sharon Gray, David Swerdlow, and Catia Ferreira all report salary from Pfizer.